The Effect of Radiotherapy on Skin Reactions in Nasopharynx Cancer Patient - Putri, Elsya Nur Fadhilla; Prakoeswa, Flora Ramona Sigit; Pramuningtyas, Ratih (Universitas Muhammadiyah Surakarta, 2024)
Nasopharyngeal cancer is a squamous cell carcinoma with a high frequency in East and Southeast Asia. Radiotherapy is the main treatment method often used in the management of nasopharyngeal cancer. Although effective in destroying cancer cells, radiotherapy often causes significant skin reactions, including radiation dermatitis, which can appear as erythema, desquamation, and even ulceration. These reactions can affect the sufferers' quality of life and interfere with the continuity of therapy. This study aims to explore factors that affect the intensity of radiation dermatitis, including location of radiotherapy and concurrent chemotherapy. In addition, radiation dermatitis management strategies, such as the use of moisturizers, topical steroid therapy, and sun protection, are packaged to accelerate the healing process and reduce symptoms. Assessment criteria such as CTCAE and RTOG are used to assess The intensity of dermal responses. It is expected that a thorough understanding of the causes and management of radiation dermatitis would improve the prognosis for patients with nasopharyngeal cancer and increase the effectiveness of therapy. More research is needed to develop more effective preventative and therapeutic measures for radiation-induced dermatitis.